Cholinergic regulation of protein phosphorylation in bovine adrenal chromaffin cells. - Haycock, J W (1988)
Chromaffin cells were isolated from bovine adrenal medullae and maintained in primary culture. After prelabeling with 32PO4, exposure of the chromaffin cells to acetylcholine increased the phosphorylation of a Mr approximately equal to 100,000 protein and a Mr approximately equal to 60,000 protein (tyrosine hydroxylase), visualized after separation of total cellular proteins in naDodSO4/polyacrylamide gels. Immunoprecipitation with antibodies to three known phosphoproteins ("100-kDa," "87-kDa," and protein III) revealed an acetylcholine-dependent phosphorylation of these proteins. These three proteins were also shown to be present in bovine adrenal chromaffin cells by immunolabeling techniques. "100-kDa" is a Mr approximately equal to 100,000 protein selectively phosphorylated by calcium/calmodulin-dependent protein kinase III, "87-kDa" is a Mr approximately equal to 87,000 protein selectively phosphorylated by protein kinase C, and protein III is a phosphoprotein doublet of Mr approximately equal to 74,000 (IIIa) and Mr approximately equal to 55,000 (IIIb) phosphorylated by cAMP-dependent protein kinase and calcium/calmodulin-dependent protein kinase I. Furthermore, 100-kDa was shown to be identical to the Mr approximately equal to 100,000 protein whose phosphorylation was increased by acetylcholine treatment. The acetylcholine-dependent increase in phosphorylation of tyrosine hydroxylase, 100-kDa, 87-kDa, and protein III required extracellular calcium and was mimicked by nicotine, veratridine, elevated K+, and calcium ionophore A23187, but not by muscarine. In addition, forskolin increased the phosphorylation of tyrosine hydroxylase, 100-kDa, and protein III, but not that of 87-kDa. Phorbol 12,13-dibutyrate increased the phosphorylation of tyrosine hydroxylase, 87-kDa, and protein III, but not that of 100-kDa. The data demonstrate that cholinergic activation of chromaffin cells increases the phosphorylation of several proteins and that several protein kinase systems may be involved in these effects.